Consumers’ knowledge and acceptance of smart clothing - Andreja Rudolf; Zoran Stjepanovič; Monika Kuharič (Communications in Development and Assembling of Textile Products, 2022)
To help innovative products breakthrough in the marketplace, it is necessary to gain consumer trust. However, consumers do not necessarily receive innovations positively and may have various concerns. Innovation involves change, and many consumers are reluctant to change or need more time to gain confidence in an innovative product, whether in terms of its usefulness, benefits, price, appearance, etc. Therefore, consumers’ lack of knowledge and acceptance of innovations may be one of the key reasons why many innovations fail to come to life in the market. Smart clothing, as a kind of wearable device that combines information and communication technologies and textile materials in a clothing system, has great potential for development and market breakthroughs today. In this study, we investigated the prevalence of smart wearable devices and smart clothing in terms of consumers' knowledge and acceptance of smart clothing by consumers. The results of the survey both serve as a guide for the development of the most desirable smart clothing and indicate the necessary communication strategies for its breakthrough in the market.